Autoestima y autocuidado - Saenz Angulo, Merly (2019)
The session ls self esteem and self-care it was realized in the are of person, family and_x000D_ human relations, for students of first grade high school in Marcial Acharan y Smith school._x000D_ The purpose of the session is that students through self- care will have positive self-esteem.